Effect of Different Water Levels on Growth and Survival Rate of Green Catfish (Hemibagrus nemurus) Larvae - Taufan Gamar Fadillah Harahap; Netti Aryani; Nuraini Nuraini (Jurnal Akuakultur SEBATIN, 2022)
The study aims to determine the effect of different water levels on the growth and survival rate of green catfish larvae reared for 40 days. This research was conducted in 8 July - 17 August 2021 at the Fish Hatchery and Breeding Laboratory, majoring in Aquaculture, Faculty of Fisheries and Marine, Riau University. The method used is experimental method using a completely randomized design (CRD) with four treatments and three replications. The treatments used were: K5: 5 cm water level, K10: 10 cm water level, K15: 15 cm water level, and K20: 20 cm water level with stocking densities 2 individual/liter. The container used is aquarium measuring 30 x 30 x 30 cm as many as 12 pieces. The feed given was silk worms (Tubifex sp.) with a dose of 40% body weight per day. The frequency of feeding carried out 4 times per day at 01.00 WIB, 07.00 WIB, 13.00 WIB, and 19.00 WIB. The results showed that different water levels had significant effect (P<0.05) on absolute weight growth, absolute length growth, specific growth rate, and survival rate of green catfish larvae. The best treatment was K5 (5 cm water level) with absolute weight growth of 2,22 g, absolute length growth of 5,54 cm, specific growth rate (SGR) of 17,54 %, and survival rate of 100%. The water quality values obtained during the study were temperature of 26,3-28,5°C, pH value of 6-7, DO value of 5-5,8 ppm, and ammonia value of 0,00021-0,00213 mg/L